Sino-Russian cooperation on the sustainable utilization of Arctic biological resources: modernizing traditional knowledge - Luo, Ying; Yang, Li; Lobanov, Andrew Alexandrovich; Andronov, Sergei Vasilevich; Lobanova, Lidiya Petrovna (Polar Research Institute of China - PRIC, 2020)
Considering the effects of global warming, humans need to face the possibility of an ice-free Arctic during summer. Russia spans Eurasia and occupies more Arctic lands than any other country. This vast area has a great variety of species, and the geography and environment of the Arctic have endowed these species with unique and valuable properties. All the world’s ancient nations have their traditional knowledge. The indigenous traditional knowledge of the Arctic and the knowledge embedded in traditional Chinese medicine are part of the world’s time-honored wisdom. Some of this ancient lore cannot be verified by modern scientific methods, but the methods are effective in practice, triggering further exploration and innovation. Russian Arctic indigenous people have a long history of using the Arctic biological resources. The use of therapeutic materials in traditional Chinese medicine has many similarities with the use of Arctic biological resources by indigenous peoples. Both types of traditional knowledge can inspire new approaches to the development of the Arctic biological resources. China and Russia are among the world’s largest countries, and it is important that they cooperate in developing the Arctic biological resources. The development of sustainable use of these resources, while updating traditional knowledge, is an urgently needed investment that requires an innovative approach.